Omsk conference on the history of the Civil War in Eastern Russia: history and development prospects - A. V. Sushko; D. I. Petin (Омский научный вестник: Серия "Общество. История. Современность")
The history of the emergence and formation, as well as the dynamics of development of the scientific and practical conference «Civil War in the East of Russia: a look through the documentary heritage», held since 2014 in Omsk, is presented. The key characteristics of past conferences are analyzed (topics and number of materials in collections, geography of authors, whether they have academic degrees, the total number of participants, etc.). The authors of the article (active members of the organizing committee) consider the conference as a current phenomenon of scientific life, realized in external and internal political circumstances that are special for Russia and its academic science. The review is addressed to a wide range of readers, including researchers in the history of historical science, historiography of the Civil War in Eastern Russia, historical memory, the history of archival affairs in Siberia and local history.